Implementing model of service learning in teaching strategic management course - Jelenc, Lara; Mujević, Denisa; Mikelić Preradović, Nives (2008)
The London communiqué (2007) emphasizes one of the goals of higher education, and that is to prepare students for their future careers and enabling their personal development. The employability of students should rise and they should have capabilities, competencies, and skills needed for the competitive job market. Therefore, the relation between universities and employers should be more strongly interwoven. Bologna process initiated the curriculum reform, introducing a student-oriented study, interactive teaching, and urges for higher level of student involvement. The students have factual knowledge, while they lack soft skills and competence to implement their knowledge in practice. Students are in a position when they finish their studies and are left without actual practical use of what they have learned and no real experiences. The model of service learning is contemporary teaching standard enabling dialogue between universities, students, and employers. Employer is facing a real-time problem, which students help to resolve while implementing theoretical knowledge learned in lectures and seminars. This paper introduces the model of service learning in teaching strategic management course. The model was developed in USA and was introduced for the first time in teaching a course of Informatics at the University of Zagreb in the academic year 2006/2007. The paper introduces the model of service learning, explains the main prerequisites of the model, and proposes the implementation in teaching Strategic management. The semester long teaching according to service learning model offers first-hand experience and reflections on the students, employers, and teacher’ s feedback, concluding about the need of this model in teaching strategic management course.
Sažetak radova je dostupan u: Proceedings of the 4th International Conference An Enterprise Odyssey : Tourism - Governance and Entrepreneurship / Galetić, Lovorka ; Čavlek, Nevenka (ur.). - Zagreb : Ekonomski fakultet Rijeka , 2008. 57-58.
Projekt MZOS
Projekt MZOS
ENG